Nonlinear Analytical Approaches for Prediction of Alternans Mediated Cardiac Arrhythmias - Kulkarni, Kanchan; Tolkacheva, Elena G. (Highlights on Medicine and Medical Science Vol. 5, 2021)
Cardiac alternans, an alternation in the action potential duration (APD), is suggested to be a precursor to lethal tachyarrhythmias such as ventricular tachycardia or ventricular fibrillation, which in turn can lead to sudden cardiac death. Linear methods for detection of alternans onset and suppression have shown limited success, predominantly due to presence of cardiac memory wherein APD prediction at any instant purportedly requires the knowledge of multiple previous APDs and diastolic intervals (DIs) to successfully characterize the present cardiac state. Taking into account the non-linear relationship between the APDs and preceding DIs, the transition from steady state to alternans has been captured successfully using non-linear analytical methods including bifurcation theory, principal component analysis and chaos control techniques. This chapter presents an overview of non-linear analytical approaches utilized for predicting the onset of alternans that hold potential to translate into preclinical modalities capable of alternans detection and control, thereby preventing fatal tachyarrhythmias and transition to sudden cardiac death. We present a preclinical evaluation using high resolution optical mapping of two novel techniques based on bifurcation analysis and eigenvalue decomposition to predict the onset of alternans. Furthermore, we correlate the spatial evolution of alternans with bifurcation parameters and dominant eigenvalues, providing a potential marker for alternans estimation.